Association of the COVID‐19 outbreak with acute stroke care in Switzerland. (4th January 2022) - De Marchis, Gian Marco; Wright, Patrick R.; Michel, Patrik; Strambo, Davide; Carrera, Emmanuel; Dirren, Elisabeth; Luft, Andreas R.; Wegener, Susanne; Cereda, Carlo W.; Kägi, Georg; Vehoff, Jochen; Gensicke, Henrik; et al.
Abstract: Background and purpose: In Switzerland, the COVID‐19 incidence during the first pandemic wave was high. Our aim was to assess the association of the outbreak with acute stroke care in Switzerland in spring 2020. Methods: This was a retrospective analysis based on the Swiss Stroke Registry, which includes consecutive patients with acute cerebrovascular events admitted to Swiss Stroke Units and Stroke Centers. A linear model was fitted to the weekly admission from 2018 and 2019 and was used to quantify deviations from the expected weekly admissions from 13 March to 26 April 2020 (the "lockdown period"). Characteristics and 3‐month outcome of patients admitted during the lockdown period were compared with patients admitted during the same calendar period of 2018 and 2019. Results: In all, 28, 310 patients admitted between 1 January 2018 and 26 April 2020 were included. Of these, 4491 (15.9%) were admitted in the periods March 13–April 26 of the years 2018–2020. During the lockdown in 2020, the weekly admissions dropped by up to 22% compared to rates expected from 2018 and 2019. During three consecutive weeks, weekly admissions fell below the 5% quantile (likelihood 0.38%). The proportion of intracerebral hemorrhage amongst all registered admissions increased from 7.1% to 9.3% ( p = 0.006), and numerically less severe strokes were observed (median National Institutes of Health Stroke Scale from 3 to 2, p = 0.07). Conclusions: Admissions and clinical severity of acute cerebrovascular events decreased substantially during the lockdown in Switzerland. Delivery and quality of acute stroke care were maintained. Abstract : Weekly admissions were registered in the Swiss Stroke Registry from 1 January 2018 to 8 June 2020. During the Swiss lockdown in 2020, the weekly admissions decreased up to 22% compared to expectations from admission trends since 2018. During three consecutive lockdown weeks, the admission rate was lower than the 5% quantile of expectations. The probability of observing at least that many extreme values without the lockdown is 0.38%.